Cost study of the preventing malnutrition in children under 2 years of age approach in Burundi and Guatemala - Richter, Susan; Iruhiriye, Elyse; Heckert, Jessica; Sununtnasuk, Celeste; Ruel, Marie T.; Leroy, Jef L.; Olney, Deanna K. (FHI 360; FANTA, 2018)
Cost studies were conducted in conjunction with the impact evaluations of these two PM2A (Preventing Malnutrition in Children under 2 Approach) programs to provide information on the total cost of the programs and estimate the cost of alternative versions of the programs. Providing cost-related information along with the benefits of alternative program versions can be useful for informing future programming activities. It is important to note that the cost analysis took into account the full scope of each program and not just the program costs related to the communities where the impact evaluations were conducted.